Reuse to Create - Joana Saes; Maria Luisa Costa; Mariana Castro; Sandro Bracchitta (Convergências - Revista de Investigação e Ensino das Artes)
This article presents a chalcography workshop using Tetra Pak, held in Castelló, Spain, as part of a Blended Intensive Program (BIP), under the Erasmus + Program, with the theme "The Unequal City". The study explores the role of universities in promoting social responsibility and sustainability, highlighting the importance of enabling students to adopt conscious and innovative practices, with a focus on the creative reuse of waste and in conscious graphic production. Using a qualitative methodology based on case studies, the work describes the dynamics of the workshop developed in the in-person phase of the BIP, which involved students and teachers from Portugal, Spain and Italy. The experience included the preparation of Tetra Pak matrices and the application of the drypoint technique, promoting dialogues between artistic practices, social issues and environmental challenges. The study concludes that the use of Tetra Pak in alternative printing techniques not only reduces waste but also reinforces the training of citizens and professionals committed to sustainability, capable of leading significant changes in society.